Influence of new feeding technology of milk dromedary camels on their dairy productivity. Issue 1 (December 2021) - Baimukanov, A B; Semenov, V G; Alibayev, N N; Ermakhanov, M N; Abuov, G
Abstract: The research aims to determine the influence of the new technology of feeding dromedary female camels on their dairy productivity. Milk camels of the I control group were kept in conditions of pasture with supplementary feeding of 3 kg of wheat bran, milk camels of the II experimental group, in addition to the main diet - pasture forage, received additional feeding with 3 kg of concentrated feed, consisting (wt.%): a mixture of grain waste - 50, cotton husk - 10, wheat - 25 and barley - 15 with a total nutritional value of 1.0 feed units, 9.46 megajoule of metabolizable energy and 90.5 g of digestible protein. Studies have shown that the dairy productivity of experimental groups of milk female camels gradually increases from the beginning of the lactation period. For 12 months of the lactation period, the dairy productivity of dairy camels in the control group was 2995.3 liters, in the II experimental group - 3236.2 liters in the III experimental group - 3467.9 liters. The average fat content of camel milk from sucking dromedary female camels, depending on the level of feeding, averages 4.22-4.39%.